Changes in coagulation and fibrinolysis markers in acute ischemic stroke treated with recombinant tissue plasminogen activator - Faßbender, Klaus; Dempfle, Carl-Erik; Mielke, Orell; Schwartz, Andreas; Daffertshofer, Michael; Eschenfelder, Christoph C.; Dollman, Martina; Hennerici, Michael G. (Stroke, 1999)
BACKGROUND AND PURPOSE: Shifts of the balance between coagulation and fibrinolysis play a crucial role in pathogenesis and treatment of cerebral ischemia. In this study, we characterized the kinetics of hemostatic abnormalities induced by acute ischemic stroke and its thrombolytic (recombinant tissue plasminogen activator [rtPA]) or anticoagulant (heparin) treatment. - METHODS: Systemic generation of molecular markers of hemostasis (fibrin monomer, D-dimer, thrombin-antithrombin complex, and fibrinopeptide 1.2) was monitored in acute ischemic stroke, and the effects of thrombolytic and anticoagulant treatments were analyzed. - RESULTS: Thrombolysis with rtPA induced a massive response of markers of coagulation activation and fibrin formation that peaked after 1 to 3 hours and persisted for up to 72 hours. In contrast, only minor hemostatic changes were induced by acute ischemic stroke itself. Administration of heparin did not significantly affect these hemostatic abnormalities. - CONCLUSIONS: This first characterization of the coagulation activation induced by rtPA treatment for acute ischemic stroke and the failure to abolish such hemostatic abnormalities by heparin may be of value for further refinement of the currently discussed thrombolytic therapy and the controversial adjunctive anticoagulant prophylaxis in stroke patients.